2021
DOI: 10.46627/sipose.v2i2.125
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Physics Concepts in Game Vehicles in the Indonesian Fantasy World

Adinda Choirunnisa',
Nauly Rahmaniyah,
Qori Aina

Abstract: Edutainment in physics learning or also known as physics-edutainment is a physics learning strategy associated with entertainment. The purpose of this article is to explore the physics concepts contained in the Indonesian Fantasy World. The research was conducted by studying literature from various sources of supporting articles. This study uses a qualitative descriptive approach, while the type of research used by the researcher is library research. Data or information in the form of articles obtained, then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Centripetal force takes the form of frictional force, gravitational force, and rope tension (Nurbaiti & Yusup, 2024). This force is in the form of gravity and rope tension that holds the load on the mini ontang-anting bench (Cahyani & Cheng, 2022;Choirunnisa' et al, 2021). So, it can be formulated as follows:…”
Section: Figure 5 Ontang-anting Mini Vehiclementioning
confidence: 99%
See 2 more Smart Citations
“…Centripetal force takes the form of frictional force, gravitational force, and rope tension (Nurbaiti & Yusup, 2024). This force is in the form of gravity and rope tension that holds the load on the mini ontang-anting bench (Cahyani & Cheng, 2022;Choirunnisa' et al, 2021). So, it can be formulated as follows:…”
Section: Figure 5 Ontang-anting Mini Vehiclementioning
confidence: 99%
“…According to Cahyani & Cheng (2022), the car is given a rubber belt so that when it crashes, it still feels comfortable because this rubber will absorb the effects of the collision. From these events, it can be concluded that when a car has mass ๐‘š 1 and another car has mass ๐‘š 2 collide with each other, it will cause a force, namely action-reaction which has the same magnitude but has a different direction, namely opposite each other (Newton's III Law) (Choirunnisa' et al, 2021). If it is assumed that there are only forces generated in the form of action-reaction and there are no external forces that affect it, it can be written: The equation shows that the effect of force objects, namely action-reaction or Newton's Third Law, creates the Law of Conservation of Momentum, which corresponds to sound in the law of conservation of momentum.…”
Section: Bom-bom Carmentioning
confidence: 99%
See 1 more Smart Citation